Os efeitos de personagens LGBTs de telenovelas na formação de opinião dos telespectadores sobre a homossexualidade - Trindade, Welton Danner (2010)
Since 2000, Brazil has had great progress about lesbian, gay, bisexual, transvestite, transsexual (LGBT) citizenship and about political, social and economic issues. Since 2003, many Latin soap operas have taken part in this scene systematically, most of them at 9.00 p.m. on Globo channel.The scripts are usually about homophobia and these people challenge of reaching equal state rights and acceptance in their society. This research aims the analysis of this matter exposure as the main issue on that kind of TV program and its influence on forming opinion about it on viewers over 16 who live in Distrito Federal. For it, and as a way to contribute to methodological debate of the studies tradition in Brazil, different from quantitative researches, it was given to 260 viewers corresponding to sex, age and social status audience a questionnaire .It s noticed the greater amount of female viewers (65%) compared to males ( 35%), which reinforces the characteristic of these soap operas as a product developed mainly for women, something that is attached to the origin of this kind of TV program is called radionovela ( a kind of romance narrated on the radio, it was a common radio program in Brazil in the first half of the 20th century, later on TV in 1951).The soap operas as much as any other kind of TV program have lost their audience in Brazil since 1951, but unconventional plots have changed it. This research was mostly based on Cultural Studies of Birmingham and Mediation Theories, by Jesús Martín Barbero, who disagrees that the message spoken by any speaker is completely comprehensible for its listeners and that the message has a complete and single meaning. On the contrary, the meaning is utter when it interacts with the listener, which is active in this process. This analysis got important contribution from the multimediation perspectives, by Guillermo Orozco Gómez, who says that it is necessary seeing the listeners from the social groups they belong to. As a conclusion, it s seen that homosexual characters shown on these soap operas have great influence on viewer´s acceptance to homosexual people, so it contributes to a change of view about this issue